Psychotropic medication use pre and post-diagnosis of cluster B personality disorder: a Quebec’s health services register cohort - Lunghi, Carlotta; Cailhol, Lionel; Massamba, Victoria; Laouan Sidi, Elhadji A.; Sirois, Caroline; Rahme, Elham; Rochette, Louis; Renaud, Suzane; Villeneuve, Evens; Koch, Marion; Biskin, Robert; Martineau, Cathy; et al. (Frontiers in Psychiatry, 2023)
Background: Cluster B personality disorders (PDs) are considered some of the most severe mental health conditions. Scarce evidence exists about the real-world utilization of psychotropics for cluster B PD individuals.We aimed to uncover trends and patterns of psychotropic medication use among individuals diagnosed with cluster B PD in the year before and after their diagnosis and to identify factors associated with medication use in a large cohort of individuals newly diagnosed with cluster B PDs.We conducted a population-based observational study using Quebec's health services register. We identified Quebec residents aged >=14 years and insured with the provincial drug plan with a first diagnosis of cluster B PD recorded between April 1, 2002, and March 31, 2019. Cluster B PD was defined with ICD-9/10 diagnostic codes. We retrieved all claims for the main psychotropic medication classes: antipsychotics, antidepressants, anxiolytics, mood stabilizers, and attentiondeficit/hyperactivity disorder (ADHD) medications. We calculated the proportion of individuals exposed to these medication classes and analyzed trends over the years using robust Poisson regression models, adjusting for potential confounders. We used robust Poisson regression to identify factors associated with medication class use.We identified 87,778 new cases of cluster B PD, with a mean age of 44.5 years; 57.5% were women. Most frequent psychiatric comorbidities in the five years before cluster B PD diagnosis were depression (50.9%), anxiety (49.7%), and psychotic disorders (37.5%). Most individuals (71.0%) received at least one psychotropic during the year before cluster B PD diagnosis, and 78.5% received at least one of these medications in the subsequent year. The proportion of users increased after the diagnosis for antidepressants (51.6-54.7%), antipsychotics (35.9%-45.2%), mood stabilizers (14.8%-17.0%), and ADHD medications (5.1%-5.9%), and remained relatively stable for anxiolytics (41.4%-41.7%). Trends over time showed statistically significant increased use of antipsychotics and ADHD medications, decreased use of anxiolytics and mood stabilizers, and a stable use of antidepressants.Conclusions: Psychotropic medication use is highly prevalent among cluster B PD individuals. We observed an increase in medication use in the months following the diagnosis, particularly for antipsychotics, antidepressants, and mood stabilizers.